Genetic Diversity of Rice vampireweed (Rhamphicarpa fistulosa) Populations in Rainfed Lowland Rice in West Africa - ADOUKONOU-SAGBADJA, Hubert (My University, 2016)
Rice vampireweed belongs to the Orobanchaceae and is found in Africa and Australia. It is a hemiparasitic weed of lowland rice genotypes and causes losses of 40 to 100% of rice grain yield. Our study addressed the genetic diversity of rice vampireweed in Benin and Senegal. The specific objectives of this research were to study the genetic diversity of rice vampireweed accessions in Benin and Senegal and the relationship between the different genotypes of rice vampireweed through agroecological areas. To achieve these objectives, the genetic diversity of rice vampireweed accessions using the AFLP technique was studied. Based on our results, dendrogram classification has distinguished four different genetic groups. The populations of Benin and Senegal are genetically diverse. Substantial genetic differentiation (GST) exists among agroecological areas within Benin and Senegal (GST¼0.17). The high genetic diversity of rice vampireweed in Benin and Senegal presents a challenge for the development of resistant rice germplasm.
Keywords: Facultative parasite; weeds; Benin; Senegal; rice vampireweed